Designing Cultural Archives and its Effective Dissemination using Social Computing - Sharma, Seemu (My University, 2016)
Social computing is a novel and emerging computing paradigm that involves applications and services that facilitate collective action and social interaction on the Internet. Being impressive, ubiquitous and entertaining, social computing is apparently affecting our lives unconsciously through the dynamics of mind. Specifically, its psychological effects on young generation have been seen, who are utmost reliant and obsessed by social computing. So, blend of culture and technology, particularly scientific aspects of culture and social computing technology is necessary in the field of cultural computing which has been the main focus of this research work. Particularly, Indian culture and young population has been considered in this work. Initially, a detailed review of social computing trends has been done. It analyzes various characteristics and forms of social computing technology and reports existing positive and negative effects of its usage. A comparative analysis of different approaches prevailing in the field of cultural computing has been done. The existing relevant Indian cultural websites have also been explored, analyzed and reported for their presence on web. Based on the literature survey, it is apparent that less availability of relevant information about ancient Indian culture and its reach to the masses are the main challenges besides numerous other issues that need to be addressed. To address these diverse challenges, a digital cultural repository, named Cultural Big Data Repository (CBDR) has been initially proposed and further designed, implemented and tested in this work. The proposed repository on culture, CBDR inspires from the compiled works of ancient system of Indian mathematics, called Vedic Mathematics. Its architecture provides efficiency in storing and retrieving cultural data in CBDR by using latest NoSQL technologies and other techniques implemented using the same. The design of the cultural repository, CBDR has been done by giving due considerations to handle cultural data generated and stored in CBDR, handling media types in CBDR and managing different kinds of users and other groups of the repository. The implementation of this work has been done on CBDR content management system which specially suits for the needs of the CBDR by using various tools of social computing paradigm. The repository has been deployed on web for its usage and various features. Finally, experiments have been conducted on CBDR to explore Internet usage pattern of its users. Validation of the CBDR system has been done with the help of a survey whose results have been analyzed. The results show that CBDR successfully and collectively provides a source of scientific knowledge of ancient India to the masses through the medium of modern technological methods.
PHD, CSED
Keywords: Cultural Computing; Social Computing; Indian Culture; Culture; Vedic Mathematics, NoSQL, Big Data, Efficient Storage and Retrieval techniques